Temperature Dependent Synthesis of Zinc Sulphide (ZnS) Nanoparticles and Its Characterization - Sharma, Prabha; Dhungana, Sujan; Rai, Rajan; Khadka, Devendra; Hitan, Dipak Kumar; Pokhrel, Megh Raj; Gautam, Surendra Kumar; Poudel, Bhoj Raj (Amrit Research Journal, 2022)
Zinc sulphide nanoparticles (ZnS NPs) were successfully synthesized by chemical co-precipitation method at 20°C and 40°C using zinc chloride (ZnCl2 ) and sodium sulphide (Na2S) as precursors. Ascorbic acid was used as a capping agent. The synthesized ZnS NPs were characterized by X-ray diffraction (XRD), UV-visible and Fourier transform infrared (FTIR) spectroscopy. UV-visible spectra showed that the bandgap of synthesized NPs was 3.8-3.9 eV at two different temperatures. XRD analysis showed the particles were present in the cubic phase with a zinc blend structure. FTIR spectra were used in the confirmation of the chemical species of the synthesized NPs. The average particle size calculated by using Debye-Scherrer’s equation at 20°C and 40°C was found to be 5.01 and 3.1 nm which indicates that the particle size was temperature-dependent.